Childhood Intussusception: A Prospective Institutional Study at BPKIHS - Shakya, VC; Agrawal, CS; Sinha, AK; Bhatta, NK; Khaniya, S; Adhikary, S (Journal of Nepal Paediatric Society, 2011)
Introduction: Intussusception is the commonest cause of bowel obstruction in infancy and childhood. The present study deals with the presentation, management and outcome of children presenting with intussusception at the Department of Surgery, B. P. Koirala Institute of Health Sciences, Dharan, Nepal. Materials and Methods: Forty-seven children presenting at Department of Surgery, B. P. Koirala Institute of Health Sciences over a 5-year period were prospectively studied. Results: There were 27 (58.6%) males and 20 (41.4%) females, with male-to-female ratio of 1.4:1. The ages ranged from 2 months to 13 years, with a median age of 30 months. The mean duration of presentation was 10.7 ± 30.66 days (range 1-180 days). The triad of abdominal pain, bloody mucoid stools and palpable abdominal mass was seen in 10 (21%) of the cases. Surgical exploration was done in 42 (89.3%) patients. The commonest lead point was non-specific hyperplastic lymph nodes, occurring in 22 (54.3%), followed by idiopathic variety (16.6%), Meckel's diverticulum (9.5%), ileocaecal junction (7.1%), submucous lipoma (4.7%), Non- Hodgkin's lymphoma (4.7%), appendix (2.3%) and a mucosal polyp (2.3%). Overall mortality rate was 6.3%. Conclusion: The presenting age group and the time of presentation are higher than other studies. The mortality rate of 6.3% is comparable to other studies in the developing world. Earlier presentation could have avoided surgery, with a higher possibility of cases being managed conservatively. Key words: Delayed diagnosis; intussusception; lead point DOI: 10.3126/jnps.v31i1.3682 J Nep Paedtr Soc 2010;31(1):6-10